Analysis of Leveraging Factors in Socio-Cultural Dimension Aspects for Sustainable Mangrove Forest Management in Aluh Aluh Besar Village, Banjar Regency - Jaya, Eddy Elminsyah (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
Banjar Regency is a Regency in South Kalimantan Province which is recorded as having a mangrove forest area. One of the villages that has mangrove forest potential is Aluh Aluh Besar Village. The aim of this research is to analyze leveraging factors in the context of sustainable mangrove forest management in the socio-cultural dimension. This research uses a quantitative and qualitative approach with a longitudinal design because it is sustainable over a relatively long period of time and follows an interactive process of various variables. The research results show that the largest leverage factor is â€œOwnership Statusâ€ with a value of 2.04 and the lowest is Environmental Knowledge (0.05). To measure sensitivity, a leverage analysis was carried out using 10 (ten) attributes. The conclusion of the research conducted shows that